Transforming architectural education: Focus on the preliminary design phase exploring architectural creativity: 3 workshops experience - Stachura, Ewa; Bar-Eli, Amos (EAAE Annual Conference Proceedings, 2025)
This paper advances innovations for the preliminary design phase, which is the core of an architecture student’s creativity and self-development toward professional responsibility. Hence, an experimental didactic module consisting of three workshops running separately or as a series is proposed for a course curriculum. “From Form to Form” delves into creativity as a foundational element in the de- sign process, cultivating inspiration and honing essential skills in model-build- ing, discourse analysis, and photography. The “Listen to the City” workshop serves as the guiding principle, which fosters a deep understanding of urban environments and the intricate web of social, cultural, and historical factors that shape them. Through these immersive city exploration and self-dis- covery exercises, students develop a mindset attuned to the complexities of urban intervention by mediating competing interests and narratives to create sustainable environments. Finally, the “VirtuSquare” student design workshop transcends the boundaries of reality, juxtaposing the familiar (known) with the remote (unknown). Participants use contemporary tools of observation and representation, navigating the blurred lines between the tangible and the virtual to anticipate bold and imaginative design solutions. The workshops facilitate a holistic approach to architectural creation, equipping participants with practical skills, creative insight, attuned mindset and techno- logical fluency.